Social stigma as an epidemiological determinant for leprosy elimination in Sitanala, Indonesia - Muhammad Hidayat Sahid; Wicaksono; Andriani Pratiwi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Leprosy has been eliminated as a public pathological state in most of development countries like Indonesia, however the social stigma to the sickness continues to be terribly high. This study was performed to research the role of social stigma as a determinant for infectious disease elimination in an exceedingly infectious disease endemic region of Indonesia. Focus cluster discussions, in-depth interviews and structured questionnaires were accustomed investigate infectious disease social stigma among lepers, their contacts and an effect cluster consisting of patients attending a hospital for reasons aside from infectious disease. consent was wanted and gained before beginning the study. Focus cluster discussions and in-depth interviews known 3 kindsof stigma; lack of vanity, social group stigma and complete rejection by society. From the 480 structured questionnaires administered, there have been over- all positive attitudes to lepers among the study population and inside the divisions (P=0.0). The proportion of participants that felt sympa- thetic with distorted lepers was 78.1% [95% confidence interval (CI): 74.4-81.8%] from a complete of 480. 300 and 99 (83.1%) respondents indicated that they may share a meal or drink at constant table with a distorted leper (95% CI: 79.7-86.5%). 103 (83.9%) participants indicated that they may have an acknowledgment and embrace a distorted leper (95% CI: 87- 87.3%). a complete of 85.2% (95.0% CI: 81.9-88.4%) participants thoroughbred that they may move with a distorted leper to the market or mosque. A high proportion of 71.5% (95.0% CI: 67.5%-75.5%) participants expressed that they may supply employment to a distorted leper. The results indicate that Sitanala 1 division had very cheap mean score of 3.3 on positive attitudes to infectious disease compared with Sitanala 2 (4.1) and Sitanala 3 (4.8) divisions.The high proportion of positive attitudes among the participants and in numerous divisions may be a positive indicator that the elimination of infectious disease social stigma is progressing within the right direction. Quantification of stigma to assess the elimination struggle may be a new analysis space publicly health.